Aplikasi Presensi Digital Berbasis GPS dengan Leaflet JS - Afrina, Nisa; Habiba, Azifa (Jurnal Algoritma, 2025)
Manual internship attendance recording is inefficient and prone to manipulation. This study aims to develop a web-based internship attendance system integrated with GPS location validation and digital document management to improve accuracy and simplify administration. The system was developed using a prototype model with PHP Native and LeafletJS for real-time location visualization. The results of implementation and qualitative evaluation show that the system functions effectively, significantly improving the efficiency of attendance recording and improving internship documentation. The main contribution of this study is to provide an integrated digital solution that combines robust location verification and document management in a single platform. The implication is the achievement of higher data accuracy and transparency, as well as significant operational efficiency, improving the discipline of interns.